Novel Approaches to Targeted Drug Delivery via Endogenous Enzyme Activation - O'Leary, Connor Joseph (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2025)
Current treatments used in cancer chemotherapy are limited due to their narrow therapeutic window, dose-limiting toxicity and low cancer-cell specificity, making the development of targeted drug delivery strategies an urgent research challenge. The overexpression of certain enzymes in cancer cells has been exploited for the specific activation of prodrugs in the tumour microenvironment, facilitating significantly improved selectivity of the active drug and reduced off-target effects. Innovative strategies applied to polymeric systems for responsive applications, depolymerisation and drug delivery systems are being developed. Such systems which are activated in response to endogenous stimuli in the tumour microenvironment represent an underexplored field in chemical biology and materials science. In addition, examples of enzyme-responsive systems generated by lithographic polymerisation techniques are very limited. In this work, the synthesis of a suite of glycomonomer conjugates and their subsequent polymerisation to form glycopolymers is presented, designed to be specifically activated by endogenous glycosidases as well as recognised by lectin and boronic acid substrates. Furthermore, the design and synthesis of various advanced self-immolative crosslinkers is reported, which are designed to be activated by endogenous beta-galactosidase, applying a previously reported prodrug activation strategy to a polymeric system. Efforts to polymerise these crosslinkers via two-photon polymerisation and bulk methods are described, aiming to generate polymer networks that would depolymerise upon enzymatic activation. Cyclic peptides such as somatostatin are attracting growing attention as therapeutics due to their favourable pharmacological characteristics, with increased metabolic stability and binding affinity as a result of their limited conformational flexibility. Both beta-galactosidase and somatostatin receptors are overexpressed in a range of tumour types. Somatostatin and its analogues have a well-defined pharmacophore which is constituted by the Phe-Trp-Lys-Thr residues of the beta-turn; modifying this sequence would be expected to generate an inactive analogue of the active peptide. Here, analogues of essential amino acids in the pharmacophore of therapeutic peptide somatostatin which bear enzyme-activated galactoside and bioreductive groups are presented. Unnatural threonine amino acid analogues are successfully synthesised and an example of a glycopeptide somatostatin prodrug analogue is reported, with preliminary biological results presented. This represents the development of a new, dual-targeted prodrug strategy which exploits the overexpression of both β-galactosidase and somatostatin receptors in certain tumour types, for targeted delivery of a peptide therapeutic.
APPROVED
Keywords: Prodrug; Peptides; Drug delivery; Polymer; Glycosidase; Responsive materials; Enzyme; Cyclic peptides; Two photon polymerisation; Galactosidase; Glucuronidase; Galactose; Glucuronic acid